Efficacy of SPECT Myocardial Perfusion Imaging (MPI) in Combination with Coronary Artery Calcium (CAC) Score for the Diagnosis of Coronary Artery Disease (CAD) - Amin, Dilruba; Ferdousi Begum, Shamim Momtaz; Mutsuddy, Pupree; Mandal, Tapati; Majumder, Sanhita; Nath, Khokon Kumar; Islam, Md Saiful (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Cardiovascular disease (CVD) is an important cause of morbidity and mortality in Bangladesh. The coronary artery calcium (CAC) score is a readily and widely available tool for noninvasive diagnosis of atherosclerotic coronary artery disease (CAD). Aims: To evaluate the diagnostic efficacy of combined CAC score with Single Photon Emission Computed Tomography (SPECT) Myocardial Perfusion Imaging (MPI) for the diagnosis of CAD. Methods: This cross sectional study was carried out in the National Institute of Nuclear Medicine & Allied Sciences (NINMAS) during July 2017 to June 2018. A total of 33 participants with known or suspected cases of CAD were included in this study who underwent SPECT MPI and CAC imaging. Statistical analyses of the results were obtained by using Statistical Packages for Social Sciences (SPSS-22). Results: Nearly half (48.5 %) of the participants belonged to age 51-60 years. Was male predominant in this study, 93.9% and 6.1% ware female. Regarding MPI 69.7% participants had severely abnormal perfusion and 21.2% had normal perfusion. According to CAC score 33.3% participants had moderate calcification in coronary artery. Significant CAD was found in 81.82% participants in Coronary Angiogram (CAG) study. Combined SPECT MPI and CAC score diagnosed significant CAD in 90.9% patents. The performance test of CAC score showed 96.3% sensitivity, 33.3% specificity, 84.8%accuracy, 86.7% positive predictive value (PPV) and 66.7% negative predictive value (NPV) for diagnosis of significant CAD. The performance test of SPECT MPI has sensitivity of 85.2%, specificity 50%, accuracy 78.8% and PPV 88.5% and NPV 42.8%. The performance test of combined SPECT MPI and CAC score, has 96.3% sensitivity, 50% specificity, 87.8% accuracy, 89.6% PPV and NPV 75%. CAC score with a cut off value of 12.5 had best combination of sensitivity 93.9% and specificity 50% for identifying the CAD missed by SPECT MPI. Conclusion: The CAC score may offer incremental diagnostic information over SPECT MPI for identifying patients with significant CAD and negative MPI results. Bangladesh J. Nuclear Med. 23(1&2): 21-28, 2020